2022
DOI: 10.1111/are.15780
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of different density restrictions reveals the potential influence mechanism on the compensatory growth of Litopenaeus vannamei

Abstract: Shrimp nursery rearing technology is increasingly being used by aquatic farmers and enterprises. Determining an appropriate density restriction in order to obtain a greater compensatory growth potential is the key to this technology. Based on the industry standards for indoor shrimp farming, three densities for Litopanaeus vannamei nursery rearing were examined (D1 [control] = 10,000 PL/m3, D3 = 30,000 PL/m3, and D5 = 50,000 PL/m3). The results showed that the D5 group had an over‐compensation growth effect, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 41 publications
(50 reference statements)
1
4
0
Order By: Relevance
“…On the other hand, determination of the specific growth rate (SGR) provides a valuable tool to identify specific periods of high growth rates ( Ricker, 1975 ). In the present study, shrimp showed a significantly higher SGR during the feeding recovery period, revealing a compensatory response, as observed in other studies conducted on the same species ( Yu et al, 2008 ; Liu et al, 2022 ) and also in the Chinese shrimp F. chinensis ( Zhang et al, 2010 ), in the Oriental river prawn Macrobrachium nipponense ( Li et al, 2009 ) and in the crayfish Cherax quaricarinatus ( Stumpf, Tropea & Greco, 2014 ; Stumpf & López Greco, 2015 ).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…On the other hand, determination of the specific growth rate (SGR) provides a valuable tool to identify specific periods of high growth rates ( Ricker, 1975 ). In the present study, shrimp showed a significantly higher SGR during the feeding recovery period, revealing a compensatory response, as observed in other studies conducted on the same species ( Yu et al, 2008 ; Liu et al, 2022 ) and also in the Chinese shrimp F. chinensis ( Zhang et al, 2010 ), in the Oriental river prawn Macrobrachium nipponense ( Li et al, 2009 ) and in the crayfish Cherax quaricarinatus ( Stumpf, Tropea & Greco, 2014 ; Stumpf & López Greco, 2015 ).…”
Section: Discussionsupporting
confidence: 90%
“…In this respect, Jobling (2010) describes that a recovery growth is a convergence between the compensatory growth and a catch-up growth. Moreover, feed restriction combined with other factors such as stocking density or temperature can also affect the compensatory response ( Stumpf et al, 2019 ; Liu et al, 2022 ; Prates et al, 2023 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Transcriptomics has assisted in the identification of RTKs in crustacean tissues, but these receptors have not been fully characterized (17,26,(31)(32)(33)(34)(35)(36)(37)(38)(39). Moreover, annotation and characterization of RTKs in diverse crustacean taxa has been hampered by databases that are limited to a relatively small number of species and taxonomic groups.…”
Section: Introductionmentioning
confidence: 99%
“…Shrimp is highly appreciated worldwide, it has a high protein content and a low percentage of fat (Duray et al, 2022;Golder et al, 2022;Liu et al, 2022;Tanjung et al, 2022). The health, safety, and overall quality of shrimp cultivation profoundly hinge on various factors, including water quality, feed composition, and the mineral content in shrimp (Kawan et al, 2019;Amir et al, 2021;Bull et al, 2021;Vieira et al, 2021).…”
Section: Introductionmentioning
confidence: 99%